Evaluation of heart rate recovery index in heavy smokers - Erat, Mehmet (Anatol J Cardiol, 2016)
OBJECTIVE: Cigarette smoking increases the risk of cardiovascular events. The heart rate recovery index (HRRI) is an indicator of autonomous nervous system function and is an independent prognostic risk factor for cardiovascular diseases. In this study, we aimed to evaluate HRRI in heavy smokers. METHODS: A total of 179 apparently healthy subjects (67 non-smokers as the control group and 112 heavy smokers) were enrolled into this prospective cross-sectional study. The presence of hypertension, diabetes mellitus, and known cardiac or non-cardiac diseases was specified as the exclusion criteria. Heavy cigarette smoking was defined as the consumption of more than one packet of cigarette per day. All subjects underwent the maximal Bruce treadmill test. HRRIs of the heavy cigarette smoker group at 1, 2, 3, and 5 min after maximal exercise were calculated and compared to those of the control group. Student t-test, chi-square test, and analysis of covariance were used for statistical analysis. RESULTS: The baseline characteristics of the two groups were similar, except for body mass index and high-density lipoprotein level. HRRIs at 1, 2, 3, and 5 min after maximal exercise were found to be significantly lower in the heavy smoker group (HRRI1: 26.78±8.81 vs. 32.82±10.34, p<0.001; HRRI2: 44.37±12.11 vs. 51.72±12.87, p<0.001; HRRI3: 52.73±11.54 vs. 57.22±13.51, p=0.018; and HRRI5: 58.31±10.90 vs. 62.33±13.02, p=0.029). CONCLUSIONS: In the present study, we found that HRRI was impaired in heavy smokers. Our results suggest that beside previously known untoward effects on vascular biology, heavy smoking also has deleterious effects on the neuro–cardiovascular system.